Efficacy of electroacupuncture in the treatment of peripheral neuropathy caused by Utidelone: Study protocol for a randomized controlled trial - Lu, Chao; Li, Guangliang; Deng, Dehou; Li, Rongrong; Li, Xiaoyu; Feng, Xukang; Wu, Taoping; Shao, Xiying; Chen, Weiji (Frontiers in Neurology, 2023)
Introduction Utidelone (UTD1) is a new chemotherapeutic drug for recurrent or metastatic breast cancer. However, it usually leads to severe peripheral neuropathy (PN) and causes numbness of the hands and feet and significant pain in patients' life. Electroacupuncture (EA) is considered beneficial in improving PN and relieving numbness of the hands and feet. This trial aims to evaluate the therapeutic effect of EA on PN caused by UTD1 in patients with advanced breast cancer. Methods and analysis This study is a prospective randomized controlled trial. A total of 70 patients with PN caused by UTD1 will be randomly assigned to the EA treatment group and the control group in a ratio of 1:1. The patients in the EA treatment group will receive 2 Hz EA three times a week for 4 weeks. The patients in the control group will take mecobalamin (MeCbl) tablets orally, one tablet each, three times a day for 4 weeks. The main outcome measures will be the evaluation scale of peripheral neurotoxicity of chemotherapeutic drugs according to the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-CIPN 20-item (EORTC QLQ-CIPN20) and the peripheral neurotoxicity assessment rating according to NCI CTCAE version 5.0. Secondary outcomes will be the quality of life scale according to the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire (EORTC QLQ-C30). The results will be evaluated at baseline, post-treatment phase, and follow-up. All major analyses will be based on the intention-to-treat principle. Ethics and dissemination This protocol was approved by the Medical Ethics Committee of Zhejiang Cancer Hospital on 26 July 2022. The license number is IRB-2022-425. This study will provide clinical efficacy data on EA in the treatment of PN caused by UTD1 and will help to prove whether EA is an effective and safe therapy. The study results will be shared with healthcare professionals through the publication of manuscripts and conference reports. Trial registration number ChiCTR2200062741.